Preventive and curative effects of Calendula officinalis infusion in a dextran sulfate sodium (DSS)-induced colitis model in BALB/c mice - Bouferkas Youcef; Haddi Abir; Amier Leila; Argungu Khadija Kabir; Belkaaloul Kawthar; Addou Samia (Archives of Biological Sciences)
Inflammatory bowel disease (IBD), including ulcerative colitis and Crohn’s disease (CD), is characterized by chronic intestinal inflammation. Current therapeutic strategies, including immunosuppressants and biologics, have limitations such as adverse effects and variable efficacy. Calendula officinalis (Co), a medicinal plant with recognized antiinflammatory and antioxidant properties, may represent a promising alternative or complementary approach. This study aimed to evaluate the preventive and curative effects of Co infusion in a murine model of ulcerative colitis (UC) induced by dextran sodium sulfate (DSS). Fifty male BALB/c mice were randomly assigned to five groups: control, DSS+water (positive), Co+DSS (preventive), DSS+Co (curative), and DSS (positive). Colitis was induced by the administration of 4% DSS in drinking water for 7 days. Co infusion (2 g/150 mL) was administered orally for 14 days. Clinical parameters, including body weight and the Disease Activity Index (DAI), were recorded. Oxidative stress markers, including myeloperoxidase (MPO), malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH), and pro-inflammatory cytokines interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and C-reactive protein (CRP), were assessed. DSS administration induced significant weight loss, inflammation, and colonic oxidative stress. Co infusion significantly attenuated these effects and reduced inflammatory and oxidative markers. The findings suggest that Co may have potential as a preventive and curative agent in IBD management.